Pemilihan Presiden Langsung Dan Dampaknya Terhadap Demokrasi Di Indonesia - Naradipa, Andro Prayogi; Firdaus, Emilda; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
One of the important principles of state of law is the principle of legality. The principleof legality is closely related to the idea of democracy and the idea of a state of law. Stateagencies are fittings state as intended by the Act of 1945, that one of them is thePresident and Vice President. As the head of state and head of government elected as apair directly by the people as mandated by the Constitution, the implementation of the2014 general election and the election of President and Vice President are the result ofthe election held directly by the people, is a manifestation of the success of the processdemocratization in Indonesia.From this background, the problem can be formulated as follows: How does the systemgeneral election of President and Vice President are directly in Indonesia ?, How is theimpact of the election of President and Vice President to democracy in Indonesia ?. Thisstudy aimed to evaluate the implementation of the general election of President and VicePresident are directly in order to strengthen the system of governance in Indonesia. Todetermine whether the election of President and Vice President are directly able to fightfor the aspirations and interests of the people of Indonesia in a ruling government. Thisresearch is a normative law (literature study), Source of data in this research issecondary data.This study uses literature study (normative law), which examines the general election ofPresident and Vice President directly, regulatory law, literature, dictionaries,newspapers, magazines, papers and the results of the problems examined. From thisstudy, the authors conclude elect the President and Vice President are directly referred toin Article 6A of the 1945 Constitution of the Third Amendment of 2001, Law No. 23Year 2003 regarding the General Election of President and Vice President as amendedinto Law No. 42 of 2008 on Elections General President and the Vice President said thatthe election was carried out in direct, public, free, confidential, honest, and fair everyfive years, and was held to elect the President and Vice-President, through elections,sovereign people elect the President and Vice-President of the expected can fight for theaspirations and interests in a governmentruling. The government in power is itself a result of the people's choice was to rule theState. Folk exercise control or supervision of the government. Thus, through the generalelection of President and Vice President through a democratic procedure of the peoplewill be able to always be involved in the political process and are directly or indirectlyassert sovereignty over state power and government through their representatives.Keywords: Direct Presidential Elections - Democracy - Indonesia